KEBERHASILAN SEKOLAH MERAIH GELAR ADIWIYATA DAPAT MENINGKATKAN KESADARAN RAMAH LINGKUNGAN SISWA DALAM HEMAT ENERGY (Study Case: SMA Negeri 8 Serang Banten) - Rachman, Indriyani; Muarif, Samsul; Santuso, Edy; Rahayu, Ida; Dahlia, Karlina Puspa; Raharjo, Slamet; Matsumoto, Toru (Universitas Pendidikan Indonesia, 2017)
One of the school's successes in reaching the title Adiwiyata is habitual school community in everyday life. These habits reflect whether they are environmentally friendly patterned or not. Adiwiyata is a program that forms the entire school community to characters that care for the environment. Creating a school that is clean, healthy, beautiful and ethics and aesthetics. With the knowledge and habits of students' awareness and eco-friendly lifestyle, it is the foundation for SMA Negeri 8 Kota Serang to be earned Adiwiyata. This study raised the issue of whether the program launched by the school for a degree Adiwiyata can increase knowledge and change the habits of students in energy efficiency. This research method using qualitative description, in which respondents were given questionnaires, interviews, and observations. However, the role that the school community is very important in realizing the success of the school to achieve Adiwiyata title. Thus the required environmental education activities that can form the students become the generation that can contribute to being part minded citizens who are environmentally.